Microfluidics-mediated self-template synthesis of anisotropic hollow ellipsoidal mesoporous silica nanomaterials. Issue 8 (15th November 2017) - Hao, Nanjing; Nie, Yuan; Tadimety, Amogha; Closson, Andrew B.; Zhang, John X. J.
ABSTRACT: Herein, a facile strategy was firstly developed to synthesize ellipsoidal mesoporous silica nanomaterials (MSNs) with well-ordered parallel channels along the short axis. A miniaturized microfluidic device with spiral-shaped channels was then chosen as a straightforward and general platform to produce the corresponding hollow counterparts of MSNs under mild conditions. Such reaction process carried out in a microfluidic system was further demonstrated to be more rapid and efficient than a conventional batch method under equivalent experimental conditions. The evolution of hollow structure can be well tuned by flow rates (i.e. etching time), providing a new paradigm for rational design and engineering of anisotropic nanostructures. GRAPHICAL ABSTRACT: IMPACT STATEMENT This study developed a straightforward and general microfluidic platform to produce hollow nanostructures, providing new routes for rational design and engineering of functional nanomaterials.